Coenzyme Q10 treatment improved visual field after homonymous quadrantanopia caused by occipital lobe infarction - Fernández-Vega, Beatriz (Am J Ophthalmol Case Rep, 2018)
PURPOSE: To report the clinical findings and management of a case of occipital lobe infarction with homonymous quadrantanopia in a patient treated with vitamins and coenzyme Q10. OBSERVATIONS: A currently 69-years-old patient presenting in 2007 left inferior quadrantanopia following a right occipital lobe stroke with initial visual field index of 82% and 79% in the right and left eyes, respectively. From 2007 to 2010 was treated with vitamin and antioxidant complexes, without specific signs of changes observed in the visual field (81% right eye, 79% left eye). In 2011 was treated for the first time with coenzyme Q10 (Active complex(®) Q10 Gold 100 mg) in addition to the vitamin and antioxidant supplementation. A promptly slight improvement of the visual field in both eyes was observed. In 2013, a remarkable improvement was noticed observing a slight scotoma where previously presented the quadrantanopia. Thereafter, in the successive one-year follow-up examinations the patient experienced an exponential improvement in the visual field with gradually fading of the scotoma. Currently the patient no longer presents any sign of quadrantanopia, with normal visual field in both eyes (99% right eye, 98% left eye). CONCLUSION AND IMPORTANCE: Spontaneous improvement more than 6 months after stroke is thought to be unlikely. However, we observed, for the first time, an amelioration of the visual field after 10 years of an occipital lobe stroke. The combination of vitamins and coenzyme Q10 (100 mg) improved the prognosis with significant recovery of the visual field, which is impossible to recover under current knowledge.